THE ROLE AND MAIN CHARACTERISTICS OF ECO TOURISM IN THE FIELD OF TOURISM OF THE REPUBLIC OF UZBEKISTAN - Jamolov Rahmonali Dilakfor o`g`li Student of Economy faculty “TIIAME” National Research University ,Tashkent ,Uzbekistan Scientific adviser : Yuldasheva Nargiza Abdukholiq qizi Senior teacher of English Department “TIIAME” National Research University ,T (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article talks about the role and specific features of eco tourism in the field of tourism in Uzbekistan. Key words: ecotourism, forestry, ecotourism development, ecotourism resources, ecotourism potential, ecotourism areas.